2007
DOI: 10.1007/s10903-007-9112-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Perceived Health and Depressive Symptoms: A Longitudinal Analysis with Older Korean Americans

Abstract: The present study examined changes in the perceived health of older Korean Americans (n = 141) over a 2-year period: 2003 (T1) and 2005 (T2). A hierarchical regression model of changes in perceived health was estimated with the following array of predictors: (1) background variables (age, gender, marital status, education, and length of stay in the United States), (2) initial perceived health (T1), (3) physical and mental health conditions at T1 (chronic conditions, functional disability, and depressive sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
(50 reference statements)
1
12
0
Order By: Relevance
“…In this study, we compared several sociodemographic characteristics, (Jang et al, 2009;Yoo & Zippay, 2012). Interestingly, in the current study, Korean older adult immigrants living in the USA demonstrated a higher HRQOL, regardless of whether or not they lived with others (spouses and/or adult child), compared to Korean older adults.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…In this study, we compared several sociodemographic characteristics, (Jang et al, 2009;Yoo & Zippay, 2012). Interestingly, in the current study, Korean older adult immigrants living in the USA demonstrated a higher HRQOL, regardless of whether or not they lived with others (spouses and/or adult child), compared to Korean older adults.…”
Section: Discussionmentioning
confidence: 73%
“…These cohabitation statistics are similar to those found in Park and Park’s () study. In both groups, those living with a spouse had the highest level of HRQOL, which supports the findings from a study of Korean older adults (Korea Institute for Health and Social Affairs, ) and older Korean adult immigrants in the USA (Jang et al ., ; Yoo & Zippay, ). Interestingly, in the current study, Korean older adult immigrants living in the USA demonstrated a higher HRQOL, regardless of whether or not they lived with others (spouses and/or adult child), compared to Korean older adults.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations